Epigenetic Targets for Therapeutic Approaches in COPD and Asthma. Nutrigenomics – Possible or Illusive - Radostina V. Cherneva; Dimitar Kostadinov (Folia Medica, 2019)
Oxidative stress generated by cigarette smoking, environmental pollution, or other noxious particles leads to epigenetic changes in the cells of the respiratory tract. They reflect cell adaptation in response to chronic exposure to external factors. Although there is no change in the genetic code, epigenetic changes may be heritable and translated from one generation to another, accumulating abnormalities and rendering cells into entirely different phenotype, causing disease. DNA methylation, post-translation histone modification, ubiquitination, sumoylation and miRNA transcriptional regulation are the major processes that are responsible for the epigenetic control of gene expression. All of them are reversible. They can be regulated by targeting specific enzymes/proteins involved in the process in order to mitigate inflammation. Chronic respiratory diseases have epigenetic signatures that affect gene expression in the lung. Targeting them provides the development of novel diagnostic and therapeutic approaches in respiratory medicine. Nutrigenomics reveals the beneficial effect of natural phytochemicals, affecting key steps in the signaling pathways of chronic respiratory diseases.